CONSTRUCTING SINGAPORE'S CULTURAL AND POLITICAL NARRATIVES: A STUDY ON LEE KUAN YEW'S CONTROL OF THE MEDIA TO BUILD SINGAPORE - Buni Yani (Soegijapranata Catholic University, 2008)
There are several ways how to understand culture - and also politics - in one country. One way is to look at the media that become the backbone of communication between the state and the people. The powerful media can be used to form people's understanding on